2003
DOI: 10.4049/jimmunol.171.6.3047
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Induces Selectively Transcriptional Activation of Cyclooxygenase-2 in HeLa Cells: Pivotal Roles of Toll-Like Receptors, p38 Mitogen-Activated Protein Kinase, and NF-κB

Abstract: Candidiasis, in its mucocutaneous form as well as in an invasive form, is frequently associated with high morbidity. PGE2, which is generated by enzymatic activity of cyclooxygenases (COXs) 1 and 2, has been shown to trigger morphogenesis in Candida albicans. In the present study, we investigated whether C. albicans altered COX-2 expression in HeLa cells. RT-PCR and Western blot analyses revealed a time-dependent biphasic behavior of COX-2 mRNA expression and COX-2 protein level. COX-1 protein remained unaffec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 54 publications
4
55
1
Order By: Relevance
“…Our data demonstrate that p38, like NF-B, is activated in a delayed kinetic upon exposure to C. albicans. This finding is in agreement with a recent report studying HeLa cells (43). The kinetics also matches findings from previous studies using LPS (39) and nickel compounds (21) as endothelial activators.…”
Section: Discussionsupporting
confidence: 93%
“…Our data demonstrate that p38, like NF-B, is activated in a delayed kinetic upon exposure to C. albicans. This finding is in agreement with a recent report studying HeLa cells (43). The kinetics also matches findings from previous studies using LPS (39) and nickel compounds (21) as endothelial activators.…”
Section: Discussionsupporting
confidence: 93%
“…COX-2 has been shown to be induced by viral, bacterial, fungal and parasitic infections [17][18][19][20][21][22]. Studies in viral infections have shown that inhibition of COX-2 is beneficial to the host [17].…”
Section: Discussionmentioning
confidence: 99%
“…This is of importance as (1) real life exposures are more like to involve mixtures of chemical and microbial agents, and (2) induction of COX-2 plays an important role in the production of immune-modulators and is widely recognized as having an important role in the onset of inflammation in the lung (39,(48)(49)(50). The findings that COX-2 contributes to the synergistic production of CXCL8 and inhibition of CXCL10 in HLF present a potential mechanism whereby exposure to PM-derived metals can exacerbate cellular responses to microbial stimuli and modulate pulmonary inflammation and its consequences such as fibrosis and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%